Saving Fable - Reintgen, Scott (Reintgen, Scott. Talespinners, 2019)
Indira Story is chosen to go to Fable and attend Protagonist Preparatory, where she hopes to learn to become a successful lead character for an author. While training as a side character, Indira discovers a menacing antagonist attacking the school and is determined to stop the evildoer.